PATHWAYS FOR BLOOD AND BOWEL CANCER PATIENTS IN THE LAST YEAR OF LIFE: DESCRIBING INPATIENT CARE PATTERNS USING ROUTINE NATIONAL DATA. Issue 1 (1st March 2014) - Kane, EV; Howell, DA; Morris, E; Johnson, M; Oliver, SE
Abstract : Introduction: The drive to deliver improved services for patients with cancer has highlighted the need for better information on care patterns. We examined the utility of linking different datasets for this purpose. Aim(s) and method(s): All acute myeloid leukaemia (AML) (ICD10 C92.0, C92.4, C92.5, C93.0, C94.0, C94.2, N=1771), myeloma (C90.0, N=2554) and colorectal cancer (C18-C20, N=18704) deaths in England during 2008 were identified from the National Cancer Data Repository (1990–2008) and linked to inpatient Hospital Episode Statistics. The numbers of admissions and days in hospital per month were calculated by disease type, and the occurrence of each patient's hospital visits relative to the time of death plotted on Gantt charts to show care patterns by consultant specialty. Results: Inpatient durations for those dying within a month of diagnosis were similar across the three cancer types (23 bed-days), while the admission rate was higher for haematological (3 per month) than colorectal cancers (1.7 per month). Patients surviving longer than one month were admitted less often and spent less time in hospital across diseases – however, haematology patients were admitted more frequently and for longer durations than those with colorectal cancer. Gantt charts showed the intensity of inpatient activity, with frequent visits to haematology for AML and myeloma patients and to oncology or surgery for colorectal cancer patients. Conclusion(s): Routine national data provides useful insights into the disease-specific inpatient care patterns associated with AML, myeloma and colorectal cancer during the last year of life.